O uso dos provérbios no desenvolvimento da competência discursiva - Souza, Camila Aragão Mesquita de (2019)
This essay, entitled The use of proverbs in the development of discursive competence, is the result of a research developed to Mestrado Profissional em Letras (Profletras) from the Universidade Federal do Ceará (UFC), under the guidance of Professor Rosemeire Selma Monteiro-Plantin. The developed research aims to contribute to the development of student discursive-phraseological competence; cooperate in valuing proverbs in mother tongue teaching; propose models of textual comprehension activities involving proverbial sentences and other texts, considering that the pedagogical approach of phraseological units has not been properly valued in the teaching of mother tongue in Brazil, which can be proved by the research already done in Fraseologia and Fraseodidática, although this reality is being transformed by these studies; collaborate with the formation of critical individuals and proficient readers; identify the level of discursive-phraseological competence of the students of the eighth grade. The essay hypothesizes that the study of proverbs in elementary school is significant for the development of student discursive-phraseological competence, having as research problem the following question: how to teach Portuguese language, using the proverbs, in order to contribute to the development of the student's discursive and phraseological competences, knowing that these expressions are, to some extent, marginalized by normative grammar, many textbooks and the process of teaching and learning language as one all? The methodology used for the development of the research-action proved successful in achieving the objectives set by the qualitative and quantitative analysis of the data obtained from the practice of activities performed in the classroom. This essay was developed based on the studies that concern the Phraseology, the discursive competence and the ideals brought by the Parâmetros Curriculares Nacionais, of 1998, considering the objectives that this document gives to Elementary School.